Answer :

(i) - 1 is the root of given equation.

Explanation - Substituting value - 1 in LHS


=


= 3 - 2 - 1


= 3 - 3 = 0 = RHS


Value satisfies the equation or LHS = RHS.


(ii) is the root of the given euation


Explanation - Substituting value in LHS


=


=


= 1 - 1 = 0 = RHS


Value satisfies the equation or LHS = RHS.


(iii) is not the root of given equation


Explanation - Substituting value in LHS


=


=


= ≠ 0 ≠ RHS


Value does not satisfy the equation or LHS ≠ RHS.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics